Wind energy conversion systems - Carvalho, José António Beleza (Neutro à Terra, 2021)
The production of electricity from wind energy presents an increased growth and sustained since 1985. Currently, there are wind generators located throughout the world whose power already reaches values exceeding 250 GW. The main technologies used in electromechanical conversion of wind energy into electric energy are based primarily on three types of electric machines: • The direct current (DC) machine; • The synchronous machine; • The induction machine. These machines work on the principles of the electromagnetic actions and reactions. The resulting electromechanical energy conversion is reversible. The same machine can be used as the motor for converting the electrical power into mechanical power, or as the generator converting the mechanical power into electrical power.